2010
DOI: 10.1111/j.1365-2303.2009.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of aspiration cytology of ovarian masses with histopathological correlation

Abstract: FNAC of ovarian masses is a minimally invasive procedure that can differentiate neoplastic from non-neoplastic ovarian lesions. It may help avoid unnecessary operations and preserve the reproductive ability in young patients. Furthermore, it also enables a satisfactory sub-categorization of ovarian tumours, which facilitates the choice of appropriate therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
29
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 21 publications
(38 reference statements)
6
29
0
3
Order By: Relevance
“…The surface epithelial group (either benign or malignant) in our study showed an excellent cytological and pathological correlation, as was also seen in the studies by Sood et al [9] and Gupta et al [10]. We had no false positive results in this category, leading to a positive predictive value of 100% in tumors in the surface epithelial category.…”
Section: Discussionsupporting
confidence: 88%
“…The surface epithelial group (either benign or malignant) in our study showed an excellent cytological and pathological correlation, as was also seen in the studies by Sood et al [9] and Gupta et al [10]. We had no false positive results in this category, leading to a positive predictive value of 100% in tumors in the surface epithelial category.…”
Section: Discussionsupporting
confidence: 88%
“…Only Freedman et al [4], and Sood et al [14] discussed the accuracy of FNAC for tumor typing similar to our study. In both studies ability for estimation of tumor type (83.8% for Sood et al, and 55% for Freedman et al) was higher than that in our study (39.4%).…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, the diagnostic accuracy for FNAC in our study was within the range reported by most of the studies like that of Bandyopadhyay et al [6], Sood et al [14], Freedman et al [4], Hemalatha et al [17], and Gupta et al [16], that were (97.06%, 98%, 96.2%, 96.3%, 92% respectively). But it was slightly higher than that reported by Khan et al [19] that was (89.9%) and Stewart et al [23] that was (86.5%), and prominently higher than that reported by Mehdi et al [13] that was (80.9%).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…According the results of their study the positive predictive value was 100% and negative predictive value 90.9% and the overall diagnostic accuracy was 96.2 % [18]. Recently Gupta et al, in a retrospective study of ultrasound-guided (US) FNAC of 584 ovarian lesions evaluated that FNAC sensitivity for a diagnosis of malignancy was 85.7%, specificity 98.0%, positive predictive value 97.7%, negative predictive value 87.7% and accuracy 92.0%.…”
Section: Discussionmentioning
confidence: 99%